IMMUNOHISTOCHEMICAL CHARACTERISTICS OF CARDIOMYOCYTES IN CHRONIC ISCHEMIC HEART DISEASE (European Journal of Interdisciplinary Research and Development, 2025)
In the immunohistochemical study of myocardium in chronic ischemic heart disease (CIHD), the following main markers were used: Desmin, SA sarcomeric actin, and the myogenic regulatory factor MyoD1 (myogenin). The desmin marker applied in this study represents the protein structures of the intermediate filaments forming the framework of myocardial myocytes, determining muscle contractility, and is expressed in both skeletal and cardiac muscles. This intermediate filament protein is mainly localized in the cytoplasm of cardiomyocytes, exhibiting an intense golden-yellow staining pattern and uniform expression in healthy muscle fibers. Cytoplasmic staining appears as homogeneous yellow coloration, which is characteristic of intact muscular components.